Evaluation of symphysis pubis and sacroiliac joint distances in skeletally immature patients: A computerized tomography study of 1020 individuals - Önder Kalenderer; Ali Turgut; Tayfun Bacaksız; Emre Bilgin; Mert Kumbaracı; Hasan Ali Akkan (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to create a reference about normal pubic symphysis and sacroiliac joint widths of children and adolescents. Methods: A total of 1020 computerized tomography axial scans of patients without pelvic injury between 2 and 18 year-old were studied. The narrowest width of pubic symphysis and bilateral sacroiliac joints were measured. Results: The average pubic symphyseal width at 2 years old boys was 6.35 ± 1.06 mm (4.88–9.13 mm). The average of right and left sacroiliac joints' widths at 2 years old boys was 4.56 ± 0.65 mm (3.59–6.07 mm) and 4.58 ± 0.66 mm (3.44–5.74 mm), respectively. The average pubic symphyseal width of 2 years old girls was 5.85 ± 1.14 mm (4.06–8.20 mm). The average of right and left sacroiliac joints' widths at 2 years old girls was found 4.36 ± 0.56 mm (3.50–5.37 mm) and 4.42 ± 0.59 mm (3.58–5.73 mm), respectively. The average pubic symphyseal width at 18 years old boys was found 3.68 ± 1.30 mm (1.90–5.79 mm). The average of right and left sacroiliac joints' widths at 18 years old boys was found 1.97 ± 0.21 mm (1.73–2.41 mm) and 2.04 ± 0.30 mm (1.70–2.65 mm), respectively. The average pubic symphyseal width at 18 years old girls was 3.92 ± 0.52 mm (2.97–4.76 mm). The average of right and left sacroiliac joints' widths at 18 years old girls was found 2.34 ± 0.40 mm (1.58–3.34 mm) and 2.33 ± 0.37 mm (1.58–3.10 mm), respectively. Conclusion: Our results suggest that one should be suspicious about pelvic injury if the width of pubic symphysis is over 10 mm and width of sacroiliac joint is over 8 mm especially in patients younger than 10 years-old. Level of Evidence: Level III Diagnostic study. Keywords: Pubic symphysis, Sacroiliac joint, Measurement, Pediatric, Computerized tomography